2022
DOI: 10.1097/nhh.0000000000001049
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Caregiver Educational Program on Interactions between Family Caregivers and Patients with Advanced COPD

Abstract: The quality of family caregiver–patient interaction plays a crucial role in the context of chronic conditions. This study investigated the effects of a caregiver educational program on interactions between family caregivers and patients with advanced chronic obstructive pulmonary disease (COPD). In this trial, 92 pairs of family caregivers and patients in a subspecialty lung care clinic located in Birjand, Iran were allocated into intervention and control groups (n = 46 per group). The intervention consisted o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In our study, family caregivers reported that they often had to learn to manage the patient's disease by trial and error. Although some studies have demonstrated the positive effects of their involvement in educational programmes (Vagharseyyedin et al., 2022), family caregivers are still rarely included in such programmes and even when they are, they have not been specifically designed to support family caregivers (Marques et al., 2021; Vagharseyyedin et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, family caregivers reported that they often had to learn to manage the patient's disease by trial and error. Although some studies have demonstrated the positive effects of their involvement in educational programmes (Vagharseyyedin et al., 2022), family caregivers are still rarely included in such programmes and even when they are, they have not been specifically designed to support family caregivers (Marques et al., 2021; Vagharseyyedin et al., 2022).…”
Section: Discussionmentioning
confidence: 99%